Smart metering technology and community participation: investigating household water usage and perceived value of hybrid water systems. Issue 1 (19th August 2021) - Fornarelli, R.; Anda, M.; Dallas, S.; Morrison, G. M.
Abstract: Hybrid water systems (HWSs) are emerging as an alternative decentralised and cost-effective approach for urban water management. Although continuous monitoring is recognised as an essential step to inform the planning and design of water services, a knowledge gap has been identified in the integration of water use monitoring, HWSs and community participation. This research compares water practices of households with and without HWSs, integrating both quantitative and qualitative data. Water use data were collected at selected households via smart meters at 30 minute intervals. R computing software was used for data analytics and dashboard visualisation. Qualitative data on water practices was collected through one-to-one interviews, on-line surveys and community workshops. On a per capita basis, sites with HWSs have a 20% lower total water demand and 41% lower mains water demand than sites without HWSs. Depending on the level of sophistication of the installed HWS, the reduction of mains water use across the participants ranged from 20% to as high as 80%. Almost all sites with HWSs were able to meet the state government targets (40–60 kL/person/y) on annual per capita mains water usage. The seasonality of rainwater supply versus the weather-independent supply of greywater was observed in the data. The qualitative data collected during community engagement highlighted the importance of establishing a personal connection between the individual and the water resource and of involving the resident in the different stages of harvesting, using and disposing of water. This is expected to contribute to a higher perceived value of the water resources by improving awareness, making knowledge more accessible, improving the transparency between the community needs and the water utility decisions. To this end, the role of digital technologies in the water sector plays a role in assisting with the paradigm shift from centralised water networks to an integrated and community-empowered, centralised-hybrid water system. HIGHLIGHTS: Analysis of water use, hybrid water systems (HWSs) and community participation. Per-capita HWSs sites total/mains water use is 20%–40% less than sites without HWSs. 20%–80% mains water demand reduction in households with HWSs. Digital technology to improve perceived value of water resources in the community. Need of a water tariff to respond to, and incentive for, water saving behaviours.